Orexin-A signaling in the paraventricular nucleus promote gastric acid secretion and gastric motility through the activation neuropeptide Y Y1 receptors and modulated by the hypothalamic lateral area. (April 2019) - Wang, Cheng; Han, Xiaohua; Sun, Xiangrong; Guo, Feiei; Luan, Xiao; Xu, Luo
Abstract: Objective: Abnormal gastric acid secretion and gastric dyskinesia are common gastroenterological ailments. Our study aims to investigate the effect of orexin-A in the paraventricular nucleus (PVN) gastric motility and gastric acid secretion. Methods: The source of orexin-A neuronal projections to the PVN were explored by retrograde tracing and fluorescence immunohistochemistry experiments. Neuronal discharge recordings of single cells were taken within the PVN. Gastric motility was recorded using a force transducer implanted into the stomach, and gastric acid secretion measured through a pyloric catheter. Results: Orexin-A-positive neuronal projections from LHA to PVN were found. Administration of orexin-A to PVN activated the firing of 63.2% NPY-excited/GD-excitatory (GD-E) neurons but suppressed the firing of 55.9% NPY-inhibited/GD-inhibitory (GD-I) neurons, promoted gastric motility and gastric acid secretion in a dose-dependent manner. Responses produced by orexin-A could be partially blocked by Y1 receptor antagonist GR-231118; Electrical stimulation to the the hypothalamic lateral area (LHA) altered NPY-sensitive/GD neuronal activity in the PVN, stimulated gastric motility and gastric acid secretion. Additionally, these effects induced by LHA electrical stimulation were blocked by administration of the OX1R antagonist SB-334867 to the PVN. Conclusion: Orexin-A from LHA neurons act on the PVN to enhance gastric motility and gastric acid secretion, with Y1 receptor signaling playing a critical role. Highlights: A portion of the LHA orexin-A- immunopositive neurons in the LHA may project their axons directly to the PVN. The PVN orexin-A signaling promotes gastric acid secretion and gastric motility mainly through the activation Y1 receptor. The LHA may participate in orexin's stimulatory effect on gastric motility and gastric acid secretion.